Exploiting advances in arc welding technology : international conference : Cambridge, UK, 30-31 March 1998 (Abington Publishing, an imprint of Woodhead Publishing, 1999)
Arc welding continues to be the predominant fabrication process for a wide range of manufacturing industries, and the conference provided a unique insight into the process developments and applications from around the world. The economic success of a fabrication is critically dependent on the selection of the most cost effective welding procedures - hence the importance of companies keeping abreast of the latest developments in arc welding technology to ensure that the most cost effective and reliable procedures are used. The papers recognise the major improvements in arc process techniques, consumables and equipment which have taken place over the last decade or so and which have enabled significant increases in manufacturing efficiently and weld quality to be achieved. The content of this book is relevant to all manufacturing industries which utilise arc welding technology, including both heavy and light fabrication and in a range of materials. It will be of value to all concerned with the cost-effective fabrication of reliable products by arc welding - welding engineers, technical managers, designers, metallurgists, production engineers and quality assurance enigneers.